Common and specific genes in ovarian clear cell carcinoma and serous carcinoma by gene expression analysis - Cao, Wenjiao; Wang, Lihua (Translational Cancer Research, 2018)
Background: Gene expression profiles differences of clear cell carcinoma (CCC) and serous carcinoma (SC) have been documented, however, these studies usually miss the specific genes changed only in SC or CCC. This study analyzes gene expression profiles of the two histological types and normal ovarian surface epithelium to determine the common and specific genes in these tumors. Methods: The gene expression profiles GSE29450 and GSE36668 were downloaded and analyzed, followed by differentially expressed genes (DEGs) analysis between ovarian cancer and normal samples. Overlap analysis was performed to identify common and specific DEGs in SC and CCC, and then these DEGs were functionally enriched. Subsequently, the protein-protein interaction (PPI) network was constructed on these DEGs and Oncomine analysis was down on select genes. Results: A set of 1,265 DEGs were common to comparisons of each of the two histologic subtypes with normal ovarian surface epithelium, such as ESPL1 and CDC25C, and they were mainly enriched in functions and pathways associated with “chromosome segregation”. In addition, 2,971 specific DEGs were identified in the development of ovarian CCC including ribosomes protein genes and other key nodes. Whereas a list of 4,181 DEGs were in SC progression, such as KIT and SYK. Conclusions: The common genes appearing on each ovarian carcinoma subtype’s comparison with normal ovarian surface epithelium may benefit to shed light on the common part of molecular mechanisms for ovarian carcinomas pathogenesis. Whereas the specific genes may provide unique targeted therapy for each histological subtype.